2021
DOI: 10.3233/jnd-200584
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with Eculizumab in Treatment-Refractory Acetylcholine Receptor Antibody-Positive Generalized Myasthenia Gravis

Abstract: Background: Although established therapies are effective in most patients with generalized myasthenia gravis (gMG), some patients do not respond or they experience intolerable adverse events, highlighting the need for better tolerated targeted therapies for treatment-refractory gMG. Objective: To describe real-world experience with eculizumab in patients with treatment-refractory acetylcholine receptor antibody-positive (AChR+) gMG. Methods: Retrospective chart review of 15 patients with treatment-refractory A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…This retrospective review also demonstrated similar safety data, with 10 mild adverse events reported. 44 …”
Section: Complement and Its Role In Myasthenia Gravis ( Fig...mentioning
confidence: 99%
See 1 more Smart Citation
“…This retrospective review also demonstrated similar safety data, with 10 mild adverse events reported. 44 …”
Section: Complement and Its Role In Myasthenia Gravis ( Fig...mentioning
confidence: 99%
“…This retrospective review also demonstrated similar safety data, with 10 mild adverse events reported. 44 A post-marketing interim analysis of 40 patients with treatment-refractory AChR+ gMG treated with eculizumab in Japan between 2017 and 2019 similarly showed reductions in mean MG-ADL and QMG scores, as well as reductions in IVIg treatments. This study also demonstrated safety data at par with the phase II, phase III, and OLE trials, with 16 adverse events reported.…”
mentioning
confidence: 99%
“…We observed improvements in both patient-reported (MG-ADL) and physician assessed (MG-MMT) outcomes as in prior studies. 1,2,[7][8][9] Notably, a clinically significant decrease occurred in MG-ADL from baseline to 1-mo follow-up and was sustained.…”
Section: Discussionmentioning
confidence: 91%
“…In general, eculizumab was well tolerated, and a change in the eculizumab treatment schedule due to the occurrence of side effects was not necessary. If the patient experiences mild symptoms, they are generally subjected to treatment with symptomatic drugs such as acetaminophen or paracetamol ( 51 ). Overall, patients discontinued treatment owing to the development of serious side effects such as MG exacerbation and myasthenic crisis.…”
Section: The Development Of Eculizumabmentioning
confidence: 99%